Macroprudential policy and aggregate demand - Teixeira, André (2022)
This paper assesses the impact of macroprudential policy (MaPP) on aggregate demand in the EU between 2000-2019. Using a difference-in-differences approach, we find that MaPP reduces household consumption and increases firm investment. These effects are relatively mild in the short run but become more pronounced in the long run. Our findings point to a weaker macroeconomic impact than suggested in previous studies.